Implicações da prova Brasil no trabalho de professores da rede de ensino de Cascavel-Pr: contradições entre as exigências das avaliações em larga escala e o currículo municipal - Zen, Rosane Toebe (Universidade Federal de São Carlos, 2018)
This doctoral thesis fits in the studies of the Public Assessment Policies of Basic Education and its main objective is to understand the repercussions of the Brazil Exam in the teaching work for the teachers of the public municipal schools of Cascavel-PR before the contradictions between the large-scale evaluation of the Exam and the municipal curriculum. The research aims specifically to: a) contextualize the economic, political and social conditions in which the Public Assessment Policies were established and implemented, considering the Brazilian Basic Education; b) analyze the development and contradictions of the Brazil Exam implementation in Cascavel-PR, understanding that the work is guided by a curriculum of its own, conceived on the basis of theoretical criticism; c) understand the limits and possibilities of the Brazil Exam to promote the emancipation of the pedagogical work. The study started from the implicated problematization of the Brazil Exam to the teaching work, in the perspective of teachers and education managers of the municipality of Cascavel-PR before the contradictions between the large scale evaluation and the municipal curriculum. It was considered as hypothesis that the demands around the large-scale exams and the limitation determined by the the working conditions and by the way in wich theachers training has taken place, have taken away the meaning of the teaching work proposed by the municipal curriculum. The research methodology is characterized as qualitative. In the data collection procedures, field research and bibliographic and documentary survey were used. Field research was conducted through interviews with teachers, pedagogical coordinators and principals of six municipal schools. Three of these institutions obtained the best IDEB scores; the other three had the lowest IDEB scores, published in October 2016. The bibliographic survey took into account theses, dissertations, articles and books to the theoretical knowledge already developed on the topic. The documentary survey was carried out through consultation of documents consisting in laws, reports, government guidelines, school documents and the teachers syndicate of the Municipal Education System of Cascavel-PR. Data analysis procedures are based on the categorization and triangulation of the different sources used. The results revealed contradictions around the working conditions and of the limits of teacher formation, initial and continuated, wich implicates negatively in the teaching work. The study also reveled potentiality, by indentifying that despite the demands determined by the Brazil Exam the teaching work have not been reduced in school content required by external assessment. There are also positive outcomes that occur when there is participation of the school community in the setting of school goals and in the collaboration to achievement of these purposes. Another positive effect is that the professionals have been defending the implementation of the municipal curriculum although limits are identified both in theoretical and practical comprehension of the pedagogical proposal intended by the document. In conclusion the Brazil Exam have taken away the meaning of the teaching work intended by the municipal curriculum, since it does not consider the limits imposed by the working conditions and by the teachers formation, initial and continuated, in the evaluation process.
Keywords: Trabalho docente; Avaliação; Prova Brasil; Currículo; Pedagogia histórico-crítica; Teaching work; Assessments; Brazil Exam; Curriculum; Historical-Critical; Pedagogy; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL